2009
DOI: 10.1093/bja/aen401
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and alcohol intervention before surgery: evidence for best practice

Abstract: Smoking and hazardous drinking are common and important risk factors for an increased rate of complications after surgery. The underlying pathophysiological mechanisms include organic dysfunctions that can recover with abstinence. Abstinence starting 3-8 weeks before surgery will significantly reduce the incidence of several serious postoperative complications, such as wound and cardiopulmonary complications and infections. However, this intervention must be intensive to obtain sufficient effect on surgical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
1
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(186 citation statements)
references
References 69 publications
3
166
1
16
Order By: Relevance
“…A recent example is the intensive peri-operative smoking cessation intervention programme that significantly reduces the complication rate and is followed by a relatively high quit rate on longer term (18). Unfortunately, the surgical group of smokers has not yet been shown to benefit from general practitioner activities (19).…”
Section: Frommentioning
confidence: 99%
“…A recent example is the intensive peri-operative smoking cessation intervention programme that significantly reduces the complication rate and is followed by a relatively high quit rate on longer term (18). Unfortunately, the surgical group of smokers has not yet been shown to benefit from general practitioner activities (19).…”
Section: Frommentioning
confidence: 99%
“…One study of the effect of smoking on implant survival in THA reported a 4.5-fold greater risk for cup or stem revision secondary to aseptic loosening in smokers [43]. Preoperative smoking cessation can reduce the rate of postoperative complications including delayed wound healing, wound infection, pulmonary, and cardiovascular [35,66,70,71].…”
Section: Introductionmentioning
confidence: 99%
“…This association has since then been re-evaluated in over 300 studies (5). A quite new aspect of the danger of smoking was introduced through a demonstration of direct relation between smoking and the outcome of treatment.…”
Section: Surgerymentioning
confidence: 99%